Safety and feasibility of laparoscopic sigmoid colon and rectal cancer surgery in patients with previous vertical abdominal laparotomy - Haksal, Mustafa; Özdenkaya, Yaşar; Atıcı, Ali Emre; Okkabaz, Nuri; Aksakal, Nihat; Erdemir, Ayhan; Civil, Osman; Öncel, Mustafa (Elsevier, 2015)
Introduction: Current study aims to analyze the impact of previous vertical laparotomy on safety and feasibility of laparoscopic sigmoid colon and rectal cancer operations. Methods: All consecutive patients who underwent a laparoscopic resection for sigmoid colon or rectal cancer were included. These aspects were abstracted and compared within no laparotomy and previous vertical laparotomy groups: demographics, perioperative aspects, pathological features and survival. Results: There were 252 patients in no laparotomy group, and 25 cases with previous vertical incisions including lower (n = 12,48%), upper (n = 7, 28%), and lower&upper (n = 2, 8%) midline and paramedian (n = 4, 16%) laparotomies. Veress insufflation and open technique were used in 19 (76%) and 6 (24%) cases, respectively, during the insertion of the first trocar in previous laparotomy group. Patients in previous laparotomy group were significantly older (59.2 +/- 13.4 vs. 66.2 +/- 0.1, p = 0.01), but gender, ASA scores, tumor and technique related factors were similar within the groups, including operation time (200 [70-600] vs. 200 [130-390] min, p = 0.353), blood loss (250 [100-1500] vs. 250 [0-2200] ml, p = 0.46), additional trocar insertion (10 [4%] vs. 3 [12%], p = 0.101), conversion (20 [7.9%] vs. 4 [16%], p = 0.25), postoperative complication (59 [23.4%] vs. 4 [16%], p = 0.06) and 30-day mortality (7 [2.8%] vs. 1 [4%], p = 0.536) rates. Oncological outcomes regarding pathological features and 5-year survival rates (65% vs. 73.2%, p = 0.678) were not different. Conclusion: The presence of a previous laparotomy does not worsen the outcomes in patients undergoing laparoscopic removal of sigmoid or rectal cancer, thus laparoscopy may be considered to be safe and feasible in these cases.
WOS: 000360993700019
PubMed ID: 26231993
Keywords: Laparoscopy; Rectal Cancer; Laparotomy; Incision